"I Don't Want to Be Here." returning from the U.S. to Mexico and emotional distress: A qualitative study - Nayelhi Saavedra Solano; Shoshana Berenzon Gorn; Jorge Galván Reyes (Elsevier, 2023)
The psychosocial impact on people who were deported to Mexico from the United States or were forcibly returned tends to be greater than on those who return voluntarily. This text examines the way the emotional discomfort experienced by a group of Mexicans who were returned in these ways is constructed, through the analysis of anthropological interviews conducted with five women and thirteen men in which the following phases were explored: pre-migration, stay in the United States, return and reinsertion. This discomfort began in the pre-migration stage, during which they experienced various forms of disempowerment caused by the socioeconomic conditions of Mexico that determine the migratory trajectory, including reintegration. If, despite the disadvantages accumulated during the pre-migration phase, migrants manage to partly reverse their material and psychosocial disempowerment during their stay in the United States, on their return to a context such as Mexico, both their disempowerment and emotional discomfort are exacerbated. We therefore consider that the harm associated with the migratory saga will continue for an indefinite number of years following a person's return to Mexico and must be treated as a social rather than a clinical problem.